2009
DOI: 10.1145/1658866.1658880
|View full text |Cite
|
Sign up to set email alerts
|

Physical interfaces for tabletop games

Abstract: IncreTable is a mixed-reality tabletop game inspired by The Incredible Machine. Users can combine real and virtual game pieces in order to solve puzzles in the game. Game actions include placing virtual domino blocks with digital pens, controlling a virtual car by modifying the virtual terrain through a depth camera interface, and controlling real robots to topple over real and virtual dominoes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Examples of studies of these kinds of hybrid tabletop gaming can be found in [16], [17] and [18]. Few studies explore how the different affordances of tangible or multi-touch interface elements affect interaction and collaboration.…”
Section: Related Workmentioning
confidence: 99%
“…Examples of studies of these kinds of hybrid tabletop gaming can be found in [16], [17] and [18]. Few studies explore how the different affordances of tangible or multi-touch interface elements affect interaction and collaboration.…”
Section: Related Workmentioning
confidence: 99%
“…Various construction kits have been proposed for applications like Computer Aided Design (CAD) [2], as educational toolkits [22], and for tabletop gaming [16]. Most technical research in this area has investigated sensing techniques to detect how the user interacts with the blocks [2,12,3].…”
Section: Introductionmentioning
confidence: 99%
“…Large horizontal interactive surfaces (or tabletop devices) are emerging as an ideal environment for these innovative hybrid games [6], [9]. Traditionally, conventional tables are popular spaces for social board-games due to their physical affordances that engage face-to-face interaction [17].…”
Section: Introductionmentioning
confidence: 99%